Validação analítica para determinação de clorpirifós e avaliação da eficiência do sistema biobed Brasil - Quatrin, Gustavo Donato (2016)
The storage and handling points of agricultural sprayers on farms are a contamination point source of punctual contamination in case of accidental spills of concentrated pesticide and / or leaks, among others. In order to avoid possible environmental contaminations, since the decade of 90 s have been developed biobed systems, where the handling of pesticides as well as agricultural implements washing are discharded on a mixture of straw, soil and peat (biomix). This mixture has the ability to retain and subsequently biodegrade pesticides. In this study was validated an analytical method applied for routine analysis to determine the organophosphate pesticide chlorpyrifos in biobeds. The method is based on 5 g sample extraction with 30 mL of acetone acidified with phosphoric acid 98:1:1 (v/v/v). After homogenization, centrifugation and filtration, 125 μL of the extract was evaporated and reconstituted in 5 mL of methanol acidified with 0.1% acetic acid. The analysis was performed on a liquid chromatographic system coupled to a tandem mass spectrometer (UPLC-MS/MS). The validation parameters evaluated were calibration curve linearity (r2), accuracy (spike and recovery %), limits of detection (LOD) and quantification (LOQ) of the instrument and the method, precision (RSD%) and matrix effect. To the linearity study analytical solutions were prepared in organic solvent and matrix extract at 0.1; 0.5; 1; 5; 20; 100; 250 ng mL-1. The recovery study was conducted on samples spiked at three concentrations (2, 10 and 50 mg kg-1) with seven replicates (n = 7) for each concentration and the values obtained were between 96 and 115% with RSD values lower than 20 % for all three concentration levels studied. The real LOQ obtained was 2 mg kg-1 and the matrix effect observed was lower than ± 20%, which demonstrates that there is not considerable suppression or enhancement in the analyte signal. The biobed system efficiently degraded chlorpyrifos in both 1) simulation of accidental spillage and 2) application of diluted pesticide solution. In the latter case, all the values obtained at the final sampling time (14 months) were below the real LOQm.